Guiana dolphins, Sotalia guianensis (Cetacea: Delphinidae), in the Paranaguá Estuarine Complex: insights on the use of area based on the photo-identification technique - Santos, Marcos C. de O. [UNESP]; Oshima, Júlia E. de F. [UNESP]; Pacífico, Eduardo dos S. [UNESP]; Silva, Ednilson da [UNESP] (Sociedade Brasileira de Zoologia, 2010)
The aim of the present study was to provide a preliminary description of habitat use by Guiana dolphins, Sotalia guianensis (Van Bénéden, 1864) in the Paranaguá Estuarine Complex (PEC), state of Paraná, Brazil. Approximately 124 km² were surveyed by small boat from April 2006 to July 2008 in the following subsets of the PEC: Canal do Superagui (~28 km²); Pinheiros Bay (~34 km²); part of Laranjeiras Bay, which included the Guaraqueçaba sub-estuary (~38 km²); and part of the Mixture Section of the PEC (~24 km²). Our efforts were unevenly distributed in the study area. During 55 survey days covering seven distinct seasons, we spent 165 hours observing 323 groups of S. guianensis. Group size varied from two individuals to aggregations as large as approximately 100 dolphins. A total of 49,921 photographs were analyzed; 15,038 (30%) were considered useful for identification purposes. A total of 182 individuals were catalogued, from which 122 (67%) were cataloged in the last three seasons, when the surveyed area was expanded. The number of individual sightings in distinct days varied from one to 16. A total of 94 individuals (51.6%) were re-sighted at least once. From the 37 individuals cataloged in the first season, 18 (48.6%) were re-sighted in the last season. Eleven individuals with 5+ sightings were always observed in the same subset of the estuary, including an individual with 13 sightings. Sixteen individuals with three to 16 sightings were observed in three of the four estuary subsets surveyed. An individual cataloged in May 2002 in a pilot study was re-sighted up to August 2006. Our preliminary results correspond to the first evidence of site fidelity for several monitored individuals; it also revealed, for the first time, the flexibility of movements throughout the entire estuarine complex by several other individuals
Keywords: Habitat use; site fidelity; cetaceans; ecology